Guía metodológica para la aplicación del lean six sigma en procesos de fabricación de plásticos en multinacionales colombianas (2019)
The present project is aimed at developing a methodological guide to implement a model of continuous improvement Lean Six Sigma in multinational organizations of the plastics sector in Colombia with a continuous production schedule or in batches, evidencing the opportunities for improvement of productive processes more In order to reduce reprocessing and non-conforming product. This approach should not be taken as a reality of all industries in the sector, since the market may vary according to the size or type of processes applied to the transformation of raw materials into products.